Simple Patents as an Instrument for the Protection of MSME Innovation in Indonesia - Jahro; Muhammad Riszki Fadli; Nurliman Prasetyo; Sofi Ananda Putri; Sahyuti Nasution (ISNU Nine-Star Multidisciplinary Journal, 2026)
Micro, Small, and Medium Enterprises (MSMEs) are strategic sectors in the national economy that play an important role in job creation and strengthening the people's economy. In practice, MSMEs often produce various simple technological innovations that are born from practical needs in the field, such as modification of production tools, improvement of work methods, and development of functional products. However, these innovations often do not receive adequate legal protection, making them vulnerable to copying and exploitation by others. Simple patents are present as one of the intellectual property rights instruments designed to provide legal protection for inventions that are simple, applicable, and have direct use value. This research aims to analyze the position of simple patents in the Indonesian patent law system and examine its role as an instrument for protecting MSME innovation. The research method used is normative legal research with a legislative and conceptual approach. The results of the study show that normatively simple patents have provided easy access to legal protection for MSMEs, both in terms of procedures and costs, but in practice their use is still not optimal. The main obstacles include low legal literacy of intellectual property rights, limited technical assistance, and the lack of integration of simple patents in MSME empowerment policies. Therefore, optimizing the role of simple patents requires strengthening policies, increasing socialization, and synergy between stakeholders so that the protection of MSME innovation can be realized effectively and sustainably.